Editorial - Graham Connelly (Scottish Journal of Residential Child Care)
Welcome to the April 2018 (Vol 17, No 1) issue of the Scottish Journal of Residential Child Care (SJRCC). As I write, news outlets worldwide, and especially in the USA, have been marking the 50th anniversary of the assassination of the cleric and civil rights leader, Dr Martin Luther King, Jr at the Lorraine Motel, Memphis on 4 April 1968. The anniversary inevitably provided an opportunity to reassess King’s legacy and progress in the USA since his death in respect of the ambitions for the human rights and social justice he articulated.